2020
DOI: 10.3390/ani10101922
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beef Production System on the Health, Performance, Carcass Characteristics, and Meat Quality of Holstein Bulls

Abstract: The aim of this study was to evaluate the effect of production system on the health, performance, carcass characteristics, and meat quality of autumn born (AB) and spring born (SB) Holstein bulls. The study involved a total of 224 Holstein bulls and was conducted over two years (2017/18, 2018/19). The four production system treatments differed during the grower period and consisted of: (i) grazed with no concentrate supplementation (G), (ii) grazed with 2 kg concentrate supplementation per day (G2), (iii) graz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…The lighter carcass weight here, being a result of the younger age at slaughter. It was also reported that total concentrate intake did not differ between bulls that were housed or grazed with ad libitum concentrates ( 50 ). Furthermore, in both studies meat quality parameters were unaffected by ad libitum production system ( 50 , 51 ).…”
Section: Bull Beef Productionmentioning
confidence: 98%
See 4 more Smart Citations
“…The lighter carcass weight here, being a result of the younger age at slaughter. It was also reported that total concentrate intake did not differ between bulls that were housed or grazed with ad libitum concentrates ( 50 ). Furthermore, in both studies meat quality parameters were unaffected by ad libitum production system ( 50 , 51 ).…”
Section: Bull Beef Productionmentioning
confidence: 98%
“…It was also reported that total concentrate intake did not differ between bulls that were housed or grazed with ad libitum concentrates ( 50 ). Furthermore, in both studies meat quality parameters were unaffected by ad libitum production system ( 50 , 51 ). Although the forage component of the diet differed, both production systems were heavily dependent on concentrates and thus the energy dense diet resulted in sufficient muscle and liver glycogen stores for anaerobic glycolysis to occur post-mortem ( 54 , 55 ).…”
Section: Bull Beef Productionmentioning
confidence: 98%
See 3 more Smart Citations